Homicide Trends and Types in 1920s-1930s Lithuania: Limitations of Official Statistics - Černevičiūtė, Sigita (Kriminologijos studijos, 2022)
This article calls into question the reliability of the official historical statistical sources of homicides in 1920s-1930s Lithuania and aims to evaluate the limitations of the mentioned sources. With this in mind, we will attempt to make some assumptions about homicide types and trends in interwar Lithuania. The Central Statistical Bureau had been publishing statistical data relevant to the investigation of homicides in Statistical Bulletins and the Statistical Yearbooks of Lithuania since 1924. These statistical sources in the homicide study were problematic due to an unclear data collection methodology, the use of different homicide terms, unrealistic definitions of urban and rural areas and changes in Lithuania’s territory and population. We cannot determine the exact rates of the 1930s homicides due to the change in the homicide terminology and its content. Between 1924-1931 the term violent deaths, except suicides, was used, and homicides were not singled out. The analysis also shows that until 1931 violent deaths included homicides and accidental deaths too. From 1932 to 1939 violent deaths were divided into 4 groups: suicide, homicide, accidents and other violence. The more detailed data of the 1930s have revealed that the most frequent victims of homicide were in the 15-29 and 29-44 age groups for men, while the 15-29 age group stands out for females. The most common method of killing was shooting. The police-published homicide statistics also reveal a problem of terminology. According to the Penal Statute of Lithuania, deprivation of life was distinguished into the crimes of homicide; infanticide; abortion; preparation to murder; attempted murder and persuasion and help to commit suicide. However, this terminology was only partially reflected in the police statistics, as between 1927-1930 the police used the term homicides and classified them into the ones committed: for-profit; during brawls; for other purposes. Infanticide was separated from homicides. Leaving out others, infanticide was the most common murder type in interwar Lithuania. Since 1931 the statistics of the police had been using the term of deprivation of life and distinguished it into the 7 types according to the motive: for-profit; during brawls; defending one’s own life or the lives of others; involuntary; infanticide; abortion and for other purposes. It did not include dead bodies found, suicides and accidental deaths. After analysing the 1931-1938 data on deprivation of life, excluding abortions, homicides would vary from 200 to 300 per year. When comparing all the deprivations of life with homicides by the cause of death, it can be concluded that these figures included preparation for murder and attempted murder as well as persuasion and help to commit suicide. Thus, due to the change in the terminology and the inclusion of attempted murders, the police statistics can be considered unreliable. Homicides are the most precisely quantitatively defined by the rates of causes of death, which in 1932-1938 Lithuania were relatively stable with an amplitude of 93-139 murders per year. On a basis of the analysis of the police statistical data, it is possible to identify at least 4 main types of homicides in interwar Lithuania: reproductive – infanticide and abortions, aggressive – killings during brawls, economic - for profit as well as unintentional homicides that happened during accidents.